2013
DOI: 10.1111/cei.12167
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and persistent levels of interleukin (IL)-17+CD4+ T cells and serum IL-17 in patients with early inflammatory arthritis

Abstract: SummaryPrognosis of patients with early inflammatory arthritis (EIA) is highly variable. The aim of this study was to compare, longitudinally and crosssectionally, the levels of cytokine-expressing cells in peripheral blood (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 41 publications
3
32
0
1
Order By: Relevance
“…In a random subset of patients in our cohort who did not receive induction treatment, longitudinal IL-17A levels did not fluctuate significantly over several years of observation. While an increase in cytokine levels over time in the general population has been described and considered to represent unhealthy aging due to underlying inflammatory processes (41), in a cohort of early arthritis patients, there was no significant change in IL-17A over a series of developmental stages (40).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a random subset of patients in our cohort who did not receive induction treatment, longitudinal IL-17A levels did not fluctuate significantly over several years of observation. While an increase in cytokine levels over time in the general population has been described and considered to represent unhealthy aging due to underlying inflammatory processes (41), in a cohort of early arthritis patients, there was no significant change in IL-17A over a series of developmental stages (40).…”
Section: Discussionmentioning
confidence: 90%
“…There is a dearth of evidence regarding the long-term course of cytokines, including IL-17A, in SLE patients (40). Zickert et al (5) showed that IL-17A levels were reduced 7 months after cyclophosphamide-based induction treatment for LN.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies aimed to address the percentage of circulating Th17 cells in pSS are currently lacking. In other chronic autoimmune diseases, such as RA, currently available data concerning conventional CD4 + Th17 cells in early phases of the disease are conflicting, reporting either increase or decrease of this T-cell subset [63,64] and it is conceivable that different disease duration in patient cohort may account for such discrepancies.…”
Section: Il-17 Axis and Th17 Cells In Pssmentioning
confidence: 99%
“…Major progress has been made in the understanding of the molecular mechanisms responsible for autoimmunity, including the identification of T helper type 17 (Th17) effector response as a key player in the pathogenesis of multiple sclerosis (MS) [2,3] and rheumatoid arthritis (RA) [4,5] and the recognition of type I interferons as critical mediators in the development of systemic lupus erythematosus (SLE) [6,7]. However, unlike the outstanding advances introduced in the treatment and prognosis of RA and MS with the development of biological agents, the field has not had a substantial breakthrough in the design of new therapies for SLE [8,9].…”
Section: Introductionmentioning
confidence: 99%